Analisa Usaha Penangkapan Ikan dengan Longline pada KM. Hiroyoshi 6 Milik PT. Intimas Surya di Benoa, Bali - Diah Ayu Safitri; I Wayan Restu; I Ketut Wija Negara (Current Trends in Aquatic Science, 2019)
This study objectives is to analyze longline fisheries business, by analyzing business feasibility aspects and operational costs and business income. The method used is descriptive quantitative, and determining respondent by purposive sampling. The data collection process is carried out for 3 months. MS. Hiroyoshi 6 which is based in Benoa Harbor which is a wooden ship measuring 120 GT, with longline fishing gear. In one year the ship can make 6 trips. The composition of the catch consists of 9 types of fish, which are dominated by tuna. The investment costs incurred are Rp. 2,750,000,000, and operating costs are Rp. 805,410,000 in one year. The average boat production yield is 73,407 kg, with revenues of Rp 4,157,275,000 and profits of Rp 1,559,465,000. The results of the business feasibility analysis, payback period 1.7, B / C ratio 1.6, and Break Even Point units of 25,000 kg and Break Even Point sales of Rp 1,415,852,000. Based on the results of the analysis, the longline fisheries business is feasible to continue.